Penerapan Sistem Akuntansi Keuangan Daerah dalam Mewujudkan Transpransi dan Akuntabilitas Keuangan Pemerintah Daerah Provinsi Jawa Barat - Diwantari, Indriyani; Siboro, Sonny Fransisco; Lutfia Putri Salsabila; Irna Susilawati (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
The implementation of the regional financial accounting system is important in realizing the financial transparency and accountability of the West Java provincial government. With a structured and measurable accounting system, financial information can be presented in a clear and timely manner to stakeholders. The West Java provincial government has taken strategic steps in strengthening its financial accounting system, including the implementation of relevant accounting standards and the use of information technology to accelerate the financial reporting process. Transparency in the accounting system allows the public to easily access financial information and understand the use of public funds. This builds public trust in government, as well as facilitates effective oversight of public financial management. Accountability is also strengthened through a good accounting system, as it allows for clear tracking of the flow of funds and accountability for their use. However, challenges remain in optimally implementing the regional financial accounting system. A strong commitment from the West Java provincial government is needed to continuously improve financial transparency and accountability, as well as to ensure that the existing accounting system runs efficiently and effectively. Thus, the implementation of the regional financial accounting system will continue to be a focus in efforts to improve public financial governance in West Java province.